Comparison of blood glucose levels from the gingival Crevicular blood and finger prick blood For diabetics & non – diabetics - E.SHUBHA POORANI,; DR.V.JAYANTH KUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Diabetes mellitus has a high prevalence rate in Indian population due to the genetic profile & lifestyle. There are several patients who go undiagnosed with diabetes mellitus in the early stages. The idea of this study was to see if the gingival crevicular blood can be used as a diagnostic marker for diabetes mellitus. The rationale for choosing gingival crevicular blood is that it is easily obtainable in the oral cavity during routine dental probing. To estimate the blood glucose levels of diabetic and non diabetic individuals using Gingival Crevicular Blood and Finger Prick Blood. To check for any correlation in the blood levels of these two sources. The sample size was Group I 30 diabetic patients and group II 30 Non diabetic patients. The blood drawn was evaluated using Accucheck (Roche Diabetics Care, India). The relevant statistical analysis were performed. The mean blood glucose in the gingival blood for group I ( Diabetics) was 58.77 ± 3.49 Standard Deviation(SD) and group II (Non Diabetics) was 29.57 ± 5.22 SD g/dl. The capillary blood glucose level for group I (Diabetics) was 220.53 ± 1.12 (SD) and for Group II was 101.77 ± 3.72 SD. The results when compared were statistically significant for differences in the Gingival Crevicular Blood and Finger Prick blood individually between group I and group II separately (p<0.05). However there was no statistically significant difference in the blood glucose levels between the gingival crevicular blood and finger prick blood within the group (P>0.05). As the intra group comparison was not statistically significant no correlation analysis was performed.This study shows that the blood glucose levels between diabetics and non diabetics had statistically significant differences between group I and group II, however no correlation was observed between the gingival crevicular blood and finger prick blood.